Psikologi Pendidikan Fase Perkembangan Anak Usia Sekolah Dasar - Wulandari, Khanifah Ayu (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
Abstract: This article discusses the deveopmental phases experienced by elementary school age children. The phases of a child’s development vary depending on the condition of the child’s body, from the physical condition to the child’s mental condition. The aim of this research is to find out and understand the developmental phases of children at elementary school age so that teachers and parents can help children increase their potential during their development period. Based on research conducted through literature study, the results obtained were that elementary school age children were in middle childhood who experienced development in terms of physical motor, cognition, socio-emosional, language and religious morals. The condition of a deveoping child requires suervision from parents and teachers so that the child develops well and wit direction.